RESERVATION SYSTEMS PARCEL IN MITRA BUANA COMPANY - Suci Megawati; Eriek Orlando, MMSI (Jurnal Sistem Informasi, 2007)
Progress in the field of computers in today's rapidly computerized in community. Thebenefit not only enjoyed by large companies but also by small companies and evenindividuals. One progress computer processing system database. Processingcomputerized database is helping companies parcel in data processing data, especiallythe large numbers. Computers are part of the activities of a large parcel companybenefits in the firm's progress. Computerization will also show the performance of thecompany to the customer that will give the impression profesionalism company bycustomers. Performance of the company can not be separated from the data andinformation quickly and accurately. Search and exchange of information in the parcelcompany to more quickly and surely will reduce the waste of time in the company.